Cimetidine in treatment of reflux oesophagitis with peptic stricture. Issue 6188 (25th August 1979) - Ferguson, R; Dronfield, M W; Atkinson, M
Abstract : Twenty patients with reflux oesophagitis causing a tight peptic oesophageal stricture entered a randomised double-blind crossover trial in which they received cimetidine, 1.6 g daily, and matching placebo each for six months. The gross endoscopic appearances of oesophagitis, though not the grades of histopathological changes, showed significant improvement during treatment with cimetidine. The need for dilatation of the strictures, however, was not reduced.